1D Chiral Lead Halide Perovskites with Superior Second‐Order Optical Nonlinearity. Issue 1 (17th October 2021) - Zheng, Yongshen; Xu, Jialiang; Bu, Xian‐He
Abstract: Chiral hybrid perovskites have shown great potential for applications in next‐generation optoelectronic devices. The intrinsic asymmetric structures of these chiral hybrid perovskites make them particularly promising for second‐order nonlinear optics (NLO). However, it remains still a challenge to obtain ideal perovskite NLO crystals featuring simultaneously large NLO coefficient, good optical transparency, high laser damage threshold, and stable physical and chemical properties, which are highly desirable for practical applications. Herein, a series is constructed of 1D chiral lead halide hybrid perovskites ( R/S ‐2‐MPD)PbX3 (2‐MPD = 2‐methylpiperidine; X = Cl, Br, I) featuring non‐centrosymmetric architectures. Among them, the ( R/S ‐2‐MPD)PbBr3 perovskites demonstrate superior performances in second‐order optical nonlinearity, including a large second‐harmonic generation coefficient (≈29.9 pm V –1 ), wide transparency region (λUV  ≈ 310 nm), high laser damage threshold (≈2.84 mJ cm –2 ), high polarization ratio (up to 96%), and robust physical and chemical stabilities. Such a balanced performance of the chiral lead halide perovskites promises their advanced application in next‐generation photonics devices. Abstract : A series of chiral lead halide perovskites ( R/S ‐2‐MPD)PbX3 have been constructed, of which ( R/S ‐2‐MPD)PbBr3 exhibits superior second‐order nonlinear opticalproperties. It features a balanced performance with a record second‐order nonlinear optical coefficient, wide transparency region, high laser damage threshold, high polarization ratio, and robust physical and chemical stabilities, which makes it a promising candidate for nonlinear photonics applications.